The Association of Cerebral Blood Flow Measured Using Extracranial Carotid Ultrasound with Functional Outcomes in Patients with Anterior Circulation Large Vessel Occlusion After Endovascular Thrombectomy—A Retrospective Study - Xin-Hong Lin; Kuan-Wen Chen; Chung-Fu Hsu; Ting-Wei Chang; Chao-Yu Shen; Hsin-Yi Chi (Neurology International)
Background: Endovascular mechanical thrombectomy (EVT) is regarded as the standard treatment for acute ischemic stroke with large vessel occlusion. Few studies have examined the evolution of cerebral flow after the acute stage of ischemic stroke. In this study, we examined the association of functional outcomes with cerebral blood flow by extracranial carotid sonography during the subacute phase after EVT and multiple prognostic variables. Methods: We conducted a single-center, retrospective, observational study between January 2018 and June 2023. Patients with acute stroke resulting from anterior circulation large vessel occlusion who underwent EVT were included. All patients underwent carotid sonography in the second week after EVT. Patients with fair (modified Rankin Scale [mRS]: 0–3) and poor outcomes (mRS: 4–6) were compared to determine the association between and identify the predictors of these factors and functional outcomes. Results: A total of 89 patients were included (female: 38 (42.7%); mean age: 69.45 ± 13.59 years). Multivariable logistic regression analysis revealed that three factors were independent predictors of fair outcomes: (1) the Alberta Stroke Program Early CT Score (odds ratio [OR]: 1.79; 95% confidence interval [CI]: 1.16–2.78; p = 0.009); (2) Thrombolysis in Cerebral Infarction 2b to 3 (OR: 4.91; 95%CI: 1.10–21.89; p = 0.037); (3) the ratio of treatment-side blood flow between the internal carotid artery and common carotid artery (QTI/QTC, OR: 45.35; 95% CI: 1.11–1847.51; p = 0.04). Conclusions: The ratio of QTI/QTC is a clinically relevant parameter as a potential predictor of favorable outcomes. This parameter can be used to formulate patient prognostic scores and help clinicians determine whether adequate cerebral perfusion is maintained during the subacute phase.